Market power in the Russian banking industry - Zuzana Fungáčová; Laura Solanko; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
The aim of this paper is to analyze bank competition in Russia by measuring the market power of Russian banks and its determinants over the period 2001-2007 with the Lerner index. Earlier studies on bank competition have focused on developed countries whereas this paper contributes to the analysis of bank competition in emerging markets. We find that bank competition has only slightly improved during the period studied. The mean Lerner index for Russian banks is of the same magnitude as those observed in developed countries, which suggests that the Russian banking industry is not plagued by weak competition. Furthermore, we find no greater market power for state-controlled banks nor less market power for foreign-owned banks. We would consequently qualify the procompetitive role of foreign bank entry and privatization. Finally, our analysis of the determinants of market power enables the identification of several factors that influence competition, including market concentration and risk as well as the nonlinear influence of size
URN:NBN:fi:bof-201408072112
Keywords: 330